Bangla Version of Lymphedema Life Impact Scale Version 2: Reliability and Validity - Mohammed Emran,; Md Israt Hasan,; Md Nazmul Alam,; Neelufar Rahman,; Md Zulfikar Ali, (KYAMC Journal, 2023)
Background: The use of disease-specific scales would be more valuable for the evaluation of the effects of lymphedema. To manage accordingly, and maintain the optimum quality of life of lymphedema patient, a validated outcome measure is helpful. Objective: To investigate the reliability and validity of Bangla Version of Lymphedema Life Impact Scale Version 2 (B-LLIS V2). Materials and Methods: A structured process that included translation, verification, compromise assessment, reverse translation, feedback, and final correction. B-LLIS V2 reliability and validity were conducted on 52 lymphedema patients. The reliability was evaluated by performing internal consistency and test–retest analyses. Its validity was assessed by comparing the B-LLIS V2 with other scales implying Pearson’s correlation. Results: Internal consistency with Cronbach’s alpha was 0.92 for total score and 0.79, 0.82, 0.80 and 0.78 for physical, psychosocial, functional, and infection respectively. The calculated overall tool score in Intra-class correlation co-efficient (ICC) for test-retest reliability was 0.94 and among subscales, the scores were 0.92, 0.95, 0.91 and 0.93 for physical, Psychosocial, functional, and infection respectively, which signified substantial reliability. The overall values of Pearson’s correlation coefficient for the construct validity were 0.91, 0.78 and 0.86 against reference standard Bengali SF-36 Health Survey, Bangla version of the Boston Carpal Tunnel Questionnaire and Bangla Start Back Screening Tool, and they all were statistically significant. Conclusions: B-LLIS V2 is a valid and reliable tool for the assessment of impairment due to lymphedema. KYAMC Journal Vol. 13, No. 04, January 2023: 198-203